A Quantitative Analysis of Microfinance Credit Facilities for MSMEs and their Impact on Liquidating Poverty in Delhi-NCR Region: With Special Reference to AU Small Finance Bank (Journal of Informatics Education and Research, 2023)
One important financial tool for earning revenue is microfinance. This study aims to ascertain how microfinance contributes to the eradication of poverty. For this purpose, 100 respondents from AU Small Finance Bank in the Delhi-NCR area of India—60 men and 40 women—were surveyed using a random sampling technique in order to collect primary data. Two different statistical techniques were used to analyze the data. The variance in the variables (livelihood, business development, income, and employment) before and after respondents' involvement in microfinance was analyzed using ANOVA, and the relationship between the dependent variable (microfinance) and independent variables (livelihood, business development, income, and employment) was ascertained using a linear regression test. The results show a strong correlation between the dependent and independent variables as well as the positive impact of microfinance institutions on reducing poverty.